Hydrophobic Drug-Triggered Self-Assembly of Nanoparticles from Silk-Elastin-Like Protein Polymers for Drug Delivery - Xia, Xiao-Xia; Wang, Ming; Lin, Yinan; Xu, Qiaobing; Kaplan, David L (Biomacromolecules, 2014)
Silk-elastin-like protein polymers (SELPs) combine the mechanical and biological properties of silk and elastin. These properties have led to the development of various SELP-based materials for drug delivery. However, SELPs have rarely been developed into nanoparticles, partially due to the complicated fabrication procedures, nor assessed for potential as an anticancer drug delivery system. We have recently constructed a series of SELPs (SE8Y, S2E8Y, and S4E8Y) with various ratios of silk to elastin blocks and described their capacity to form micellar-like nanoparticles upon thermal triggering. In this study, we demonstrate that doxorubicin, a hydrophobic antitumor drug, can efficiently trigger the self-assembly of SE8Y (SELPs with silk to elastin ratio of 1:8) into uniform micellar-like nanoparticles. The drug can be loaded in the SE8Y nanoparticles with an efficiency around 6.5% (65 ng doxorubicin/μg SE8Y), S2E8Y with 6%, and S4E8Y with 4%, respectively. In vitro studies with HeLa cell lines demonstrate that the protein polymers are not cytotoxic (IC50 > 200 μg/mL), while the doxorubicin-loaded SE8Y nanoparticles showed a 1.8-fold higher cytotoxicity than the free drug. Confocal laser scanning microscopy (CLSM) and flow cytometry indicate significant uptake of the SE8Y nanoparticles by the cells and suggest internalization of the nanoparticles through endocytosis. This study provides an all-aqueous, facile method to prepare nanoscale, drug-loaded SELPs packages with potential for tumor cell treatments.